ANALISIS KETERLAKSANAAN PRAKTIKUM KIMIA DI LABORATORIUM PROGRAM STUDI PENDIDIKAN KIMIA UNIVERSITAS TANJUNGURA PONTIANAK - Aladawiyah, Aladawiyah; Masriani, Masriani; Sartika, Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study was to describe the implementation of chemistry practice in Chemistry Laboratory Education Program of University Tanjungpura Pontianak. The type of this study was descriptive involving 81 students. The instruments used were questionnaires, interviews and observation. Data collection techniques used were direct observation, direct communication techniques and questionnaires. The result of data analysis showed the implementation of chemistry practice in terms of; (1) students response the implementation of the chemictry practice of 73.34%; (2) students response to the role and effectiveness of lecturer's guidance of 36.35%; (3) students response to assistant role is 62,98%; (4) students response to the condition of the equipment and the availability of the practicum material by 70.56%; (5) assistant response to the lecturer's role during the practicum activity was 48.89%; (6) assistant response to equipment condition was 42.96%; (7) assistant response to material condition 85.93%; (8) assistant responses to the constraints it faces 38.30%; (9) the students and assistant response the laboratory role of 66.17%; (10) assistant and students responses to practical guidebook of 83.04%. The implementation of chemistry practice in the laboratory of Chemistry Education Study Program averaged 60.85% with sufficient category.Â Keywords: Implementation of chemistry practice, chemistry laboratory, chemistry practice